2020
DOI: 10.15294/usej.v9i3.41541
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Quizizz As An Online Assessment Application for Science Learning in The Pandemic Era

Abstract: In the current pandemic era, learning process must be counduct online, including for assessment. To support online assessments, it is necessary to use information technology. A good and valid application for online assessment offered in this study is Quizizz. The purpose of this study is todetermine student responseapplication of online exams using the quizizz.The research subjects were students of science education, Universitas Negeri Semarang. The exam is a midterm of astronomy course. The method of research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…The use of Quizizz in the teaching and learning process indicates that there are changes in the process. Based on the study by Akhtar et al (2019) and Darmawan et al (2020), the findings revealed that teachers had a positive attitude toward Quizizz and were expected to employ it in the learning process in the future. The study by Akhtar et al (2019) also found that the teacher's age influenced his or her desire to use Quizizz.…”
Section: Implication Of the Use Of Quizizzmentioning
confidence: 99%
“…The use of Quizizz in the teaching and learning process indicates that there are changes in the process. Based on the study by Akhtar et al (2019) and Darmawan et al (2020), the findings revealed that teachers had a positive attitude toward Quizizz and were expected to employ it in the learning process in the future. The study by Akhtar et al (2019) also found that the teacher's age influenced his or her desire to use Quizizz.…”
Section: Implication Of the Use Of Quizizzmentioning
confidence: 99%
“…Penelitian lain menyebutkan bahwa quizizz mudah dipakai, mengurangi kecurangan dan menyenangkan, serta mahasiswa tidak merasa kesulitan dan tegang. Terlebih lagi quizizz memotivasi mahasiswa agar rajin membaca serta meningkatkan keterlibatannya di kelas (Darmawan, Daeni and Listiaji, 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…IPA merupakan salah satu mata pelajaran dasar yang menanamkan dan mengembangkan dalam diri siswa pengetahuan, keterampilan, sikap dan nilai-nilai ilmiah, serta rasa cinta dan hormat terhadap kebesaran Tuhan Yang Maha Esa (Hillmayr et al, 2020;Sukarini & Manuaba, 2021). Tujuan mempelajari sains adalah untuk mendorong pertumbuhan dan perkembangan intelektual siswa, serta mengembangkan pemikiran kritis dan rasional sehingga siswa dapat menguasai konsep-konsep Putu Lusi Antari / Modul Elektronik Berbasis Project Based Learning Pembelajaran IPAS untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar ilmiah dan hubungan antar konsep dalam kehidupan sehari-hari (Budiasa & Gading, 2020;Darmawan et al, 2020). Pentingnya pembelajaran IPA tentu guru perlu merancang pembelajaran yang menarik bagi siswa.…”
Section: Pendahuluanunclassified